EFFECT OF Curcuma xanthorrhiza ENRICHED FERMENTED PASTE FEED ON GROWTH PERFORMANCE AND SURVIVAL OF GIANT GOURAMI (Osphronemus goramy) LARVAE - Rambe, Syahdila Anjani Ramadina; Asiah, Nur; Aryani, Netti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
The growth of gourami (Osphronemus goramy) larvae is often hampered by the limited availability of natural food such as tubifex worms. The use of fermented paste feed enriched with Curcuma xanthorrhiza Roxb is expected to be an effective alternative. The research was conducted from June to August 2024 at the Fish Hatchery and Breeding Laboratory of Universitas Riau. This study aims to evaluate the effect of fermented paste feed enriched with C.xanthorrhiza on the growth performance and survival of O. goramy. A 40-day experiment was conducted using a completely randomised design (CRD) with five treatments: P1 (Tubifex/control), P2 (0 g/kg), P3 (6 g/kg), P4 (9 g/kg), and P5 (12 g/kg) temulawak. Growth, survival, feed response, and water quality were analyzed. The results showed that P3 significantly improved growth and survival compared to the other paste treatments, with weight gain (0.31 g), length gain (2.11 cm), specific growth rate (7.86%/day), and survival (76%). The best feed response was observed in P1 and followed by P3. Higher doses (P4 and P5) had a negative impact on performance. Fermented paste feed enriched with 6 g/kg C.xanthorrhiza showed potential as a partial alternative to Tubifex in rearing gourami larvae